Predisposing factors of chronic low back pain (CLBP) among sedentary office workers (SOW) in Nairobi, Kenya - Mukandoli, Kumuntu (University of the Western Cape, 2013)
Magister Scientiae (Physiotherapy) - MSc(Physio) === Chronic low back pain is a highly prevalent condition in industrialized nations. It is associated with activity limitations, disability, has significant economic impact on society and incurs personal cost. Today's working environment increasingly demands more time spent sitting due to computerization and other advances in technology. Sitting for hours without taking breaks may influence posture, and alignment of the lumbar spine. Therefore, it may influence low back pain. Kenya as a developing country has an increasing number of people involved in sedentary work. The aim of this study was to identify the predisposing factors of chronic low back pain among sedentary office workers in Nairobi. The main objectives were to establish the prevalence of chronc low back pain; to determine the possible predisposing factors of chronic low back pain and to determine the impact of chronic low back pain on work related quality of life among sedentary office workers in Nairobi, Kenya. === South Africa